The Role of the Tissue Factor Pathway in the Hypercoagulable State in Patients with the Antiphospholipid Syndrome - Amengual, Olga; Atsumi, Tatsuya; Khamashta, Munther A.; Hughes, Graham R. V. (Thrombosis and Haemostasis, 1998)
The antiphospholipid syndrome (APS) is characterised by both arterial and venous thrombosis, recurrent pregnancy loss and thrombocytopaenia in association with antiphospholipid antibodies (aPL). To explore further the pathogenesis of thrombosis in APS, we evaluated the behaviour of tissue factor (TF) pathway in patients with APS. Plasma antigen levels of soluble TF and tissue factor pathway inhibitor (TFPI), a physiological regulator of TF dependent coagulation activation, were measured in 57 APS patients (36 primary and 21 secondary to systemic lupus erythematosus). Significantly elevated levels of both TF and TFPI were found in APS patients compared with 25 healthy controls (279 ± 15 vs. 217 ± 17 pg/ml, p = 0.01; 56.24 ± 2.00 vs. 47.92 ± 2.22 ng/ml, p = 0.01, respectively), suggesting in vivo upregulation of TF pathway in patients with APS. By flow-cytometry, monocytes from a healthy donor displayed higher TF antigen expression when incubated in the presence of APS plasmas than in control plasmas (24.23 ± 3.11 vs. 12.78 ± 1.57%, p = 0.002). Peripheral blood mononuclear cells (PBMC) also expressed more procoagulant activity (PCA) when incubated in the presence of APS plasmas than in control plasmas (1.80 ± 0.12 vs. 1.35 ± 0.054, p = 0.001) implying that TF up-regulation in APS was reproducible in vitro. Human monoclonal anticardiolipin antibodies induced PCA on PBMC and also TF mRNA on both PBMC and human umbilical vein endothelial cells shown by reverse-transcription polymerase chain reaction. These data strongly suggest that the TF pathway is implicated in the pathogenesis of aPL related thrombosis.